Sustainable supplier selection and order allocation: a fuzzy approach. Issue 9 (1st September 2020) - Khoshfetrat, Sahar; Rahiminezhad Galankashi, Masoud; Almasi, Maryam
ABSTRACT: This research develops a fuzzy, multi-objective, multi-product and multi-period mathematical model for sustainable supplier selection and order allocation in the automotive industry. The problem has been investigated in previous studies, but order allocation in fuzzy environments has attracted less attention. To fill this gap, this research integrates sustainable supplier selection and order allocation with inflation, risk and fuzzy uncertainties. The most important criteria of sustainable supplier selection are developed to select the suppliers. The supplier selection process is conducted using an analytical hierarchy process. The order allocation process determines the optimum purchasing quantity of items from each supplier in each period. To achieve this, six objective functions, total cost, economic score, environmental score, social score, inflation rate and risk level, and the related constraints are considered in the model. An approach to a solution and sensitivity analysis are also provided. The results identify the best suppliers and optimum order allocation.